2014
DOI: 10.1002/ccd.25318
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with balloon angioplasty for recurrent coarctation in neonatal univentricular and biventricular norwood‐type aortic arch reconstructions

Abstract: Recurrent coarctation following NTAR is more common in 2V patients than in SV patients. BA for recurrent coarctation has similar success in both groups and should continue to be utilized in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…Factors associated with higher rates of RC after BA included smaller patients and older age at the time of Norwood procedure [16]. In our study, 88% of patients who ultimately underwent SI for RC had previously undergone BA, which is consistent with estimates from prior studies that 15–20% of patients would be nonresponders to BA . This also suggested BA being the first line treatment of RC for most operators and SI would be considered if unsatisfactory BA results.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Factors associated with higher rates of RC after BA included smaller patients and older age at the time of Norwood procedure [16]. In our study, 88% of patients who ultimately underwent SI for RC had previously undergone BA, which is consistent with estimates from prior studies that 15–20% of patients would be nonresponders to BA . This also suggested BA being the first line treatment of RC for most operators and SI would be considered if unsatisfactory BA results.…”
Section: Discussionsupporting
confidence: 88%
“…Although typically attempted first, BA to treat RC is not uniformly acutely successful and often does not provide durable gradient relief. Studies have suggested a high success rate of BA but variable freedom of re‐intervention . Factors found to contribute to successful BA were larger balloon size, lower initial peak‐to‐peak gradient and larger diameter of descending aorta in one study .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We recently described the outcomes of transcatheter intervention for recurrent coarctation in this population [18]. The aims of this study were to describe the surgical outcomes and risk factors for recurrent coarctation after NTAR in patients with SV and those with 2V anatomy.…”
mentioning
confidence: 99%